Enhancement of NADPH availability for coproduction of coenzyme Q10 and farnesol from Rhodobacter sphaeroides. (1st February 2020) - Xu, Man; Wu, Hongxuan; Shen, Peijie; Jiang, Xianzhang; Chen, Xueduan; Lin, Jinxin; Huang, Jianzhong; Qi, Feng
Abstract: Coenzyme Q10 (CoQ10 )—an essential cofactor in the respiratory electron transport chain—has important pharmaceutical and healthcare applications. Farnesol (FOH)—an acyclic sesquiterpene alcohol—has garnered interest owing to its valuable clinical and medical benefits. Here, the coproduction of CoQ10 and FOH in Rhodobacter sphaeroides GY-2 was greatly improved through the enhancement of intracellular NADPH availability. Transcription of pgi, gdh A, and nuocd was, respectively, inhibited using RNA interference to reduce intracellular NAD(P)H consumption. Moreover, zwf, gnd, and zwf  +  gnd were overexpressed to enhance the pentose phosphate pathway, resulting in improved NADPH availability in most metabolically engineered R. sphaeroides strains. RSg-pgi with RNAi of pgi combined with overexpression of gnd produced 55.05 mg/L FOH that is twofold higher than the parental strain GY-2, and 185.5 mg/L CoQ10 can be coproduced at the same time. In conclusion, improved carbon flux can be redirected toward NADPH-dependent biosynthesis through the enhancement of NADPH availability.